Assessment of RESipy module in delineation of kaolin formation deposits using electrical resistivity tomography - Daniel Eshimiakhe; Raimi Jimoh; Joseph Orojah Osumeje; Kolawole Muideen Lawal (Discover Geoscience)
Abstract In order to identify potential zones for clay mineral (kaolinite) in Kankara, Northwest Nigeria, 2D ERT survey lines were deployed across potential site and collated to form a 3D ERT model. Although field surveys using this method is relatively straight forward, it requires the application of inverse methods prior to any interpretation. Several established non-commercial inversion codes exist, but they typically require advanced knowledge to use effectively. ResIPy was developed to provide a more intuitive, user-friendly, approach to inversion of geoelectrical data, using an open source graphical user interface (GUI) and a Python application programming interface (API). This paper highlights the rationale and structure behind the interface, before demonstrating its capabilities in delineating and identifying potential zones for Kaolinite. The inversion result showed three lithological layers the overburden, weathered and fresh basement. The overburden layer showed a resistivity value in the range of 500–800 Ωm, at a depth of 1–6 m. Low resistivity values could be observed to intrude the overburden layer, and this could be attributed to Kaolin mineral. The weathered basement showed a resistivity range of 400–650 Ωm, at a depth range of 10–20 m. The Kaolin mineral can be seen to be hosted in the weathered basement, with resistivity values of 30–150 Ωm. By promoting transparency, reproducibility, and accessibility, the ResIPy open source software contributes to the advancement of geophysical research and exploration endeavors.